Enrichment and characterization of PCB-degrading bacteria as potential seed cultures for bioremediation of contaminated soil - Sviličić Petrić, Ines (Array, 2007)
Summary: The main objective of our study was to obtain seed cultures for enhancing the transformation of polychlorinated biphenyls (PCBs) in contaminated soil of the transformer station in Zadar, Croatia, damaged during warfare activities in 1991. For enrichment, six soil samples were collected from different polluted areas and microcosm approach, stimulating the growth of biphenyl-degrading bacteria, was employed. Enrichment experiments resulted in the selection of two fast growing mixed cultures TSZ7 and AIR1, originating from the soil of the transformer station and the airport area, respectively. Both cultures showed significant PCB-degrading activity (56 to 60 % of PCB50 mixture was reduced after a two-week cultivation). Furthermore, the cultures displayed similar PCB-degrading competence and reduced di-to tetrachlorobiphenyls more effectively than penta- to heptachlorobiphenyls. Strain Z6, identified as Rhodococcus erythropolis, was found to be the only culture member showing PCB-transformation potential similar to that of the mixed culture TSZ7, from which it was isolated. Based on the metabolites identified in the assay with the single congener 2,4,4'-chlorobiphenyl, we proposed that the strain Z6 was able to use both the 2,3-and 3,4-dioxygenase pathways. Furthermore, the identified metabolites suggested that beside these pathways another unidentified pathway might also be active in strain Z6. Based on the obtained results, the culture TSZ7 and the strain Z6 were designated as potential seed cultures for bioremediation of the contaminated soil